2008
DOI: 10.1523/jneurosci.2500-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Brainstem Inhibition during Anticipated Pelvic Visceral Pain Correlates with Enhanced Brain Response to the Visceral Stimulus in Women with Irritable Bowel Syndrome

Abstract: Cognitive factors such as fear of pain and symptom-related anxiety play an important role in chronic pain states. The current study sought to characterize abnormalities in preparatory brain response before aversive pelvic visceral distention in irritable bowel syndrome (IBS) patients and their possible relationship to the consequences of distention. The brain functional magnetic resonance imaging (fMRI) blood oxygen level-dependent (BOLD) response to anticipated and delivered mild and moderate rectal distentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
176
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(204 citation statements)
references
References 56 publications
23
176
3
2
Order By: Relevance
“…In particular, consistent reports of sex-related differences in amygdala responses have been reported during anticipation of aversive emotional stimuli in healthy subjects (Buchel et al, 1998;Cahill, 2006;Mackiewicz et al, 2006;Sarinopoulos et al, 2006) and IBS patients (Berman et al, 2008;Naliboff et al, 2003) and amygdala activity is associated with the cognitive and affective modulation of pain (Carrasquillo and Gereau, 2007;Neugebauer et al, 2004).…”
Section: Statistical Analysis Overviewmentioning
confidence: 73%
“…In particular, consistent reports of sex-related differences in amygdala responses have been reported during anticipation of aversive emotional stimuli in healthy subjects (Buchel et al, 1998;Cahill, 2006;Mackiewicz et al, 2006;Sarinopoulos et al, 2006) and IBS patients (Berman et al, 2008;Naliboff et al, 2003) and amygdala activity is associated with the cognitive and affective modulation of pain (Carrasquillo and Gereau, 2007;Neugebauer et al, 2004).…”
Section: Statistical Analysis Overviewmentioning
confidence: 73%
“…[12][13][14][15]18 Furthermore, resting state fMRI study performed on IBS patients demonstrated increased spontaneous neuronal activity in visceral afferent processing regions, while decreased regional brain activity in cognitive and pain regulatory regions. 21 To date, most neuro-imaging studies performed in response to visceral pain among IBS patients have been carried out in Western countries and female patients [10][11][12][18][19][20][22][23][24][25][26][27][28][29] (Table 1). However, in some Asian countries including India, a large proportion of patients with IBS are males.…”
Section: Introductionmentioning
confidence: 99%
“…The pivotal finding from these studies indicated that the central mechanisms mediating the stress-induced phenotypes following chronic intermittent psychological stress involved increased CRF, particularly in limbic brain regions (Myers and Greenwood-Van Meerveld, 2012;Tran et al, 2013). Limbic brain regions of IBS patients, including the amygdala and extended amygdala, exhibit hyperactivity in response to stress, negative effect, and colorectal stimuli when compared with controls (Berman et al, 2008;Bonaz et al, 2002). Interestingly, when IBS patients were challenged with vascular infusions of CRF, there was a greater activation of the extended amygdala in response to colorectal stimuli, suggesting an important role for CRF-mediated mechanisms in the extended amygdala in IBS pathophysiology (Tanaka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%